Design and Development of Patent System in Pharmaceutical Industry: Examining the Effectiveness and Challenges of Patent System in the Indian Pharmaceutical Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This thesis aim is to study the design and development of pharmaceutical industry in India with respect to its patent system, analyse the opinion of expertsprofessionals regarding the effectiveness of the existing Patent Act and Rules in policing and enforcing safeguards against abuse of Patents and identify the problems pertaining to enforcement of patents specifically with respect to pharmaceutical industry. The present study focuses on the design and growth of the pharmaceutical industry in relation to its patent system. It is evident from the frequency test that majority of respondents (73.14 percent) suggested that disclosure of source and origin of genetic material should be mandatory.